Diagnostic modalities x-ray and CT chest differ in the management of thoracic injury - Chapagain, D; Reddy, DJ; Shah, S; Shrestha, KG (Journal of College of Medical Sciences-Nepal, 2015)
Objective: To observe difference in the management of blunt trauma to the chest on the basis of conventional xray and computerised tomography of the chest. Methods: This prospective study was conducted between December 2011 to October 2012 in COMS in Bharatpur,a tertiary referral centre in central Nepal . Clinically stable thoracic injury patients were first evaluated with chest x-ray and the management on this basis was recorded. The findings of the CT chest were assessed and the type of management on the basis of CT was also recorded. Outcome was assessed in terms of mortality, morbidity, hospital and ICU stay with respect to the management on the basis of chest x-ray and CT scan. Results: Of the 129 patients, 74.4% were male and 25.6% were female with the patients ranging in age from 7 to 87 years (mean = 40.41 years). The most common mechanism of trauma to the chest was as a result of a motor vehicle accident (69.8%), followed by fall injury (20.2%). X-ray chest diagnosed rib fracture in 62%, haemothorax in 37%, pneumothorax in 27%, lung contusion in 10% and haemopneumothorax in 21% patients. Similarly CT chest diagnosed rib fracture in 86%, haemothorax in 54%, pneumothorax in 36%, lung contusion in 30% and haemopneumothorax in 30% patients. Mean hospital stay was 9.5 days in the group of patients having management on the basis of x-ray chest relative to mean stay of 10.2 days in the CT- chest group. In the management on the basis of xray group, there was a mean ICU stay of 2.8days compared to mean stays of 3.2 days in CT chest group. Conclusion: Though CT scan of the chest is more informative and differs the management of the blunt chest trauma, one should not forget to advise the cost effective, easily available and initial guiding agent, xray chest for early management of the chest injury patient. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12764 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 22-31